2017
DOI: 10.4028/www.scientific.net/kem.745.77
|View full text |Cite
|
Sign up to set email alerts
|

Metallosis - Literature Review and Particular Cases Presentation

Abstract: Metallosis is an adverse event developed in relation with an orthopedic implant. It was brought into attention by metal on metal total hip arthroplasty. Lately, cases were diagnosed in total knee, total elbow, and spinal surgery. Metallic debris - released because of wear or corrosion - start an inflammatory response in a chronic condition. Beside local effects, systemic effects are also described; among them toxic effects, neurological and psychiatric, alteration in thyroid and heart function, skin rushes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Correlation of all these signs and symptoms, radiological features, elevated CRP, ESR, LTT levels, and elevated blood, serum, and urine metal ions levels may help in diagnosing metallosis. 12 Although the quality control is ensured during the manufacturing of the implants, the probability of metal leaching in surrounding tissues is not ruled out. 13 Chang et al reported approximately 5.3% incidence of the metallosis after total hip arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation of all these signs and symptoms, radiological features, elevated CRP, ESR, LTT levels, and elevated blood, serum, and urine metal ions levels may help in diagnosing metallosis. 12 Although the quality control is ensured during the manufacturing of the implants, the probability of metal leaching in surrounding tissues is not ruled out. 13 Chang et al reported approximately 5.3% incidence of the metallosis after total hip arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Metallosis is a well-described phenomenon in the total hip arthroplasty (THA) literature, with an incidence of 1%-3% per year [1][2][3]. Briefly, the term encompasses the gross observation of inflammation, deposition of metallic debris, and soft-tissue necrosis resulting from metal wear at the taper junction of a prosthesis [4]. Pseudotumors are aseptic soft-tissue masses, seen traditionally in metallosis of metal-on-metal prostheses but may also be seen in a variety of implant types [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the term encompasses the gross observation of inflammation, deposition of metallic debris, and soft-tissue necrosis resulting from metal wear at the taper junction of a prosthesis [4]. Pseudotumors are aseptic soft-tissue masses, seen traditionally in metallosis of metal-on-metal prostheses but may also be seen in a variety of implant types [3,4]. Systemic metal toxicity is a less common, but serious, sequela of metallosis.…”
Section: Introductionmentioning
confidence: 99%
“…Metallosis, current issue in the field of orthopedics, is defined as a medical condition involving deposition and built up of metal debris in the periprosthetic soft tissues results from the surface deterioration of MoM bearings in orthopedic implants [26]. It occurs due to wear, corrosion particles and release of metallic nanoparticles and metal ions into the periprosthetic surrounding tissue of prosthese implant and was first seen in the setting of the fixation of fractures with metal implants [27].…”
Section: Orthopedic Metallosismentioning
confidence: 99%